Preliminary study related the incidence of methylprednisolone pulse therapy in patients visited multiple sclerosis clinic located at the Isfahan kashani hospital - Zahra Tolou-Ghamari; Vahid Shaygannejad; Fereshteh Ashtari (International Journal of Preventive Medicine, 2013)
Background: To manage relapsing-remitting multiple sclerosis (MS) in the course of acute exacerbations, methylprednisolone (MP) (Medrol or Solu-Medrol), has the ability to lock the injured blood-brain barrier and decrease irritation in the central nervous system. The aim of this preliminary study was to investigate the frequency and time interval related to MP pulse therapy in patients with MS. Methods: This Study is conducted in the MS clinic of the Isfahan Kashani hospital, that was carried out on patients (n = 901) from June 2011 to December 2012. Patients who visited MS clinic just for once disinterested from analysis. According to the incidence of MP pulse therapy in females and males, two groups were made. Group 1 included patients with 2-3 times and Group 2 included patients with more than 4 times pulse therapy. Demographical data, pharmacological variables including number and time interval related to pulse therapy for each individual were recorded in dBase. The statistical analyses of d-Base were performed using SPSS. Results: 901 patients in 1592 occasions were studied. The mean age of patients was 34.6 years old (ranged: 8-87 years old). 586 patients included 465 females and 121 males visited MS clinic just for once. 245 females in 797 occasions and 70 males in 209 occasions received pulse therapy with a mean of 4 times (ranged: 2-11 times). 51.1% and 48.9% of patients received MP pulse therapy for two and more than two up to 11 times respectively. In the 70% of the patients′ time interval between pulse therapy was with a mean of 137 days (ranged: 28-480 days). C onclusions: For pulse therapy, it seems that the female subjects refer to clinic are approximately 3.7 times higher than male subjects. To reduce the demand of patients to pulse therapy, disease management could be rationalized on the basis of illness expansion and its correlation to inter and intra individual variability. Finally, to understand the effectiveness of pharmacotherapy, in MS population (Isfahan/Iran), clinical neuropharmacology in relation to better understand of the individualized pharmacokinetics could be useful.